Correction: Lichterfeld et al. Porcine Nose Atrophy Assessed by Automatic Imaging and Detection of Bordetella bronchiseptica and Other Respiratory Pathogens in Lung and Nose. Animals 2024, 14, 3113 - Hanna Lichterfeld; Sara Trittmacher; Kathrin Gerdes; Kathrin Schmies; Joaquín Miguel; Irene Galé; Alba Puigredon Fontanet; Isaac Ballarà; Krista Marie Tenbrink; Isabel Hennig-Pauka (Animals)
In the original publication [...]